Filipino Domestic Workers and Their Capacity Development. (November 2019) - Loh, Jennifer; Estrellado, Alicia F.
This study explored the day-to-day experiences of female Filipino domestic workers in Singapore, including their working conditions, employee–employer relationships, and psychological health. In-depth interviews were conducted with 18 women. Using grounded theory, the emergent themes revealed high levels of variation, both within and between women, suggesting that the quality of domestic workers' lives depends largely on the personal characteristics of their employers or the workers themselves, rather than on any system of protection. More importantly, participants displayed positive and resilient coping strategies which enabled them to thrive despite restrictive circumstances. Implications pertaining to capabilities and empowerment development were discussed.